PERSEPSI SISWA TERHADAP PENGGUNAAN MEDIA DIGITAL DALAM PEMBELAJARAN IPA KELAS VI IBNU QOYYIM SDIT JAMI’ATUL MUSLIMIN DUMAI - Syadidah Khansa Rafikin; Dea Mustika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify students’ perceptions of the use of digital media in sixth-grade science learning at Ibnu Qoyyim SDIT Jami’atul Muslimin Dumai. The research employed a descriptive qualitative approach with data collected through questionnaires, interviews, observations, and documentation. The research subjects were sixth-grade students and the science teacher, supported by additional informants such as the principal and other teachers. Data were analyzed using method and source triangulation. The findings indicate that students have positive perceptions of digital media, particularly Quizizz and animated videos. Questionnaire results show high scores on indicators of ease of use (85.43%), material mastery (84.78%), learning satisfaction (86.12%), activeness (85.21%), motivation (86.04%), and overall perception (86.52%), all categorized as “Good.” Interview and observation results further confirm that digital media enhance enthusiasm, participation, motivation, and assist in explaining abstract concepts. Quizizz also supports fast and interactive evaluation. This study concludes that digital media play an effective role in improving the quality of science learning by enhancing students’ understanding, motivation, and engagement.